Rhabdomyosarcoma Arising in a Giant Congenital Melanocytic Naevus: Case Report and Literature Review - Tirelo M. Pitjadi; Reubina Wadee; Wayne Grayson (MDPI AG, 2019)
Giant congenital melanocytic naevi (GCN) are rare, disfiguring lesions which carry a significant risk of malignant transformation. Melanoma is the most common malignancy documented in association with these lesions. Although exceedingly rare, other malignant neoplasms, including mesenchymal tumours such as rhabdomyosarcoma (RMS), may complicate GCN. This report documents a fatal embryonal RMS arising in a GCN on the distal left lower limb of a 4-month-old female infant, who had ipsilateral inguinal lymph node metastases at the time of presentation. To date there have been only 7 prior reports in the English literature of RMS complicating GCN. Differential diagnoses include small cell melanoma, rhabdoid melanoma, and melanoma with divergent RMS differentiation. A distinction between the latter and de novo RMS arising in GCN may have potential prognostic and therapeutic implications.